Taxonomical characteristics of Greek maple (Acer heldreichii Orph.) on Trebević in Bosnia and Herzegovina (Republic of Srpska) - Cincar Siniša; Perović Marko; Novaković Marijana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2025)
Mountain Trebević in Bosnia and Herzegovina (Republic of Srpska) represents the nortwestern border of the distribution of Greek maple (Acer heldreichii Orph.) an endemic and relic taxon of Balkan Peninsula. Taxonomical research of this species, based on the charactersitics of leaves of 10 normally grown trees was done in this paper. The presence of two varieties is confirmed: var. heldreichii and var. macropterum, and within var. macropterum, three forms were found: f. typicum, f. dissectum and f. rotundiloba. Significant taxonomic variability of the species at the studied site will increase the probability of population survival on the studied locality, especially under conditions of climate change, and facilitate its in situ conservation.